Identifikasi Value Proposition Design (VPD) pada Usaha Olahan Bawang Merah Goreng Superbram (Studi Kasus pada KWT Putri Manunggal Desa Srikayangan Kecamatan Sentolo) - Rohmah, Fatkhiyah; Lubis, Fadli Akbar; Samhina, Lina; Pramudita, Anggun; Cahyani, Aulia Putri Nur; Qayyum, Azka Aulia; Bahagia, Muhammad Dhafa Putra; Destriani, Rahmatia (Jurnal Bisnis Tani, 2025)
This study aims to design a Value Proposition Design (VPD) for the fried shallot product, Superbram, managed by the Women's Farmers Group (KWT) Putri Manunggal in Dusun Pergiwatu Wetan, Kulon Progo. Using the Customer Profile and Value Map approach, this research identifies the alignment between customer needs and the value offered by the product. The results show that Superbram provides benefits to customers through the authentic savory taste of local shallots, practical packaging, and product availability on e-commerce platforms. Additionally, Superbram successfully alleviates consumer concerns by using preservative-free raw materials and offering affordable prices. The appropriate application of VPD will help this business improve its competitiveness and expand its market share by continuously adapting the product to meet customer needs and expectations.